ANALISA LOGAM BERAT CU PADA RAMBUT YANG BERDOMISILI DI WILAYAH LUBUK BEGALUNG DENGAN METODA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Aini, Hidayatul (rc-institut, 2019)
Environmental pollution by heavy metals can cause toxic hazards to humans. Heavy metals in the human body usually accumulate in several organs such as kidneys, liver, nails, adipose tissue, and hair. Heavy metals last longer in hair, so analysis of heavy metals through hair is more accurate. This study aims to determine the differences in copper (Cu) levels in hairs of various workers based on age, profession and long exposure to the environment using atomic absorption spectrophotometry (AAS). the highest Cu content obtained is 1.8252 mg/L in children aged 12 years. from the results obtained, the older the age of a person the less Cu content in his hair.